Peran Dewan Pengawas Syariah terhadap Kepatuhan Syari’ah Pada Lembaga Fintech Syari’ah - Hadi, Wildan; Rozalinda, Rozalinda; Bahar, Muchlis; Wira, Ahmad (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
This research aims to analyze the role of the Sharia Supervisory Board (DPS) in sharia compliance at sharia fintech institutions in Indonesia and identify the problems that occur. This research uses a library study method with a secondary data analysis approach from various sources such as articles, journals and previous research. The research results show that DPS has a significant role in ensuring sharia compliance through periodic supervision, implementation of DSN-MUI fatwas, and product and service development. However, various challenges were found such as weak special supervision mechanisms for sharia fintech and non-compliance with sharia principles in several institutions such as Investree, Dana Syariah, Peer to Peer Lending Syariah. This research recommends increasing DPS capacity, strengthening regulations, and better collaboration between DPS and relevant authorities to minimize sharia violations in the fintech sector. Thus, this research contributes to strengthening the sharia supervision system and supports the sustainable growth of sharia fintech.